2018
DOI: 10.3389/fendo.2018.00427
|View full text |Cite
|
Sign up to set email alerts
|

3,5-Diiodothyronine: A Novel Thyroid Hormone Metabolite and Potent Modulator of Energy Metabolism

Abstract: Over 30 years of research has demonstrated that 3,5-diiodo-L-thyronine (3,5-T2), an endogenous metabolite of thyroid hormones, exhibits interesting metabolic activities. In rodent models, exogenously administered 3,5-T2 rapidly increases resting metabolic rate and elicits short-term beneficial hypolipidemic effects; however, very few studies have evaluated the effects of endogenous and exogenous T2 in humans. Further analyses on larger cohorts are needed to determine whether 3,5-T2 is a potent additional modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 87 publications
0
41
0
Order By: Relevance
“…The TH metabolite 3,5-T2, possibly formed from its precursor T3 (Figure 1), has recently attracted great interest for several reasons (3,9,15). 3,5-T2 has been considered the main biological active metabolite of T3, formed via further phenolic ring deiodination from T3 (Figure 1).…”
Section: 5-t2 Is a Further Endogenous Th Metabolite With Thyromimetmentioning
confidence: 99%
See 1 more Smart Citation
“…The TH metabolite 3,5-T2, possibly formed from its precursor T3 (Figure 1), has recently attracted great interest for several reasons (3,9,15). 3,5-T2 has been considered the main biological active metabolite of T3, formed via further phenolic ring deiodination from T3 (Figure 1).…”
Section: 5-t2 Is a Further Endogenous Th Metabolite With Thyromimetmentioning
confidence: 99%
“…Most of these studies were performed in severely hypothyroid, mostly rat models, and 3,5-T2 doses were administered acutely as well as chronically. Unfortunately, no information had been published on 3,5-T2 concentrations reached in the circulation or in those target tissues like liver, where beneficial effects such as antisteatotic activity and increased lipid metabolism were reported (15,17,28,89,90). The first evidence for rapid T3-independent effects of 3,5-T2 on mitochondrial activity and oxygen consumption was provided by Horst et al (16), who observed rapid stimulation of oxygen consumption in isolated perfused livers, removed from hypothyroid rats.…”
Section: 5-t2 Mechanism Of Action Involves Canonical Tr Signaling Amentioning
confidence: 99%
“…A further problem arises from the degree of purity of commercial preparations of 3,5-T2, used as standards in the measurements; these preparations are, indeed, frequently contaminated with T3 [20,204]. Even with these limitations, 3,5-T2 is now widely considered a bioactive molecule with dose-dependent effects on physiological regulatory functions [20,59,113,191,[204][205][206][207][208][209][210][211].…”
Section: The 35-diodothyronine (35-t2) As a Hormonementioning
confidence: 99%
“…Even with these limitations, 3,5-T2 is widely considered a bioactive molecule [20,59,113,191,[204][205][206][207][208][209][210][211]. Thus, in summary, the field is very promising and might offer important advancements in the therapy of obesity and related pathologies.…”
Section: The Ins and Outs Of 35-t2 Researchmentioning
confidence: 99%
“…As a part of TH metabolism, Dio enzymes are proposed to catalyze the production of physiologically active 3,5-diiodothyronine (3,5-T 2 ) [139]. 3,5-T 2 is present in significant concentrations in human serum [141] and seems to have important implications in the regulation of energy metabolism, with a direct effect on mitochondria as the most likely mechanism [139,[141][142][143] ( Figure 6). So far, serum 3,5-T 2 concentrations have been associated with some pathophysiological states in humans, mainly related to glucose and lipid metabolism [144].…”
Section: Effects Of Estradiol On Tsh Cells In Males and Putative Chanmentioning
confidence: 99%